INNOVATION OF MATERNITY PILLOW DESIGN WITH LAVENDER AROMATHERAPY ON SLEEP QUALITY OF PREGNANT WOMEN IN THIRD TRIMESTER - Rahmayanti, Rini; Yani Maidelwita; Fira Gusri Amelia; Rahmat Syarief (Institute for Research and Community Service of Health Polytechnic of Kerta Cendekia, Sidoarjo, 2025)
Background: Good sleep quality plays an important role in maintaining maternal health during pregnancy and providing sufficient energy for labor. However, physiological changes such as increased uterine size, physical discomfort, and elevated progesterone levels often lead to sleep disturbances in pregnant women, particularly in the third trimester. One effort to improve maternal sleep quality is by increasing comfort through an innovative maternity pillow design equipped with lavender aromatherapy. Purpose: This study aimed to develop a maternity pillow design integrated with lavender aromatherapy as a supportive intervention to improve sleep quality among pregnant women. Methods: This study employed a pre-experimental method using a one-group pre–post test design and a research and development (R&D) approach. The R&D stages included literature review, system and product design, product development and manufacturing, expert validation, system testing, and analysis. Sleep quality was assessed using a structured questionnaire. The research was conducted over a one-year period. Results: The findings showed that maternal self-efficacy increased from 41 before the intervention to 59.8 after the intervention, with a p-value of 0.000 (p≤0.05), indicating a significant influence of the Android-based application intervention “cakoASI.id” on the self-efficacy of breastfeeding mothers. Conclusion: The evaluation results indicated that the Maternity Pillow Design was categorized as very high, effectively improved sleep quality among third-trimester pregnant women, and was feasible and successfully tested in the field